2018
DOI: 10.3390/molecules23112935
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Relation between Quantum Chemical Descriptors and Empirical Constants of Polychlorinated Compounds

Abstract: Quantum chemical descriptors and empirical parameters are two different types of chemical parameters that play the fundamental roles in chemical reactivity and model development. However, previous studies have lacked detail regarding the relationship between quantum chemical descriptors and empirical constants. We selected polychlorinated biphenyls (PCBs) as an object to investigate the intrinsic correlation between 16 quantum chemical descriptors and Hammett constants. The results exhibited extremely high lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Choosing appropriate molecular descriptors, such as the octanol−water partition coefficient (K OW ) and dissociation constant (pK a ), is a popular technique for compiling the structure information and physicochemical attributes of organic compound into digital form in QSAR modeling. 25,26 However, we found that ln k obs exhibited poor correlations to ln K OW in manganese oxo-anion oxidation (R 2 < 0.22), suggesting that the hydrophobic nature of PC was not responsible for the selective oxidation of it by manganese oxoanions (Figure S4). In addition, the pK a descriptor showed weak associations for the kinetic rates of PC oxidation by manganese oxo-anions (R 2 < 0.70, Figure S5), implying that proton transfer was not the prevailing mechanism for these oxidation processes.…”
Section: Chemicalsmentioning
confidence: 86%
“…Choosing appropriate molecular descriptors, such as the octanol−water partition coefficient (K OW ) and dissociation constant (pK a ), is a popular technique for compiling the structure information and physicochemical attributes of organic compound into digital form in QSAR modeling. 25,26 However, we found that ln k obs exhibited poor correlations to ln K OW in manganese oxo-anion oxidation (R 2 < 0.22), suggesting that the hydrophobic nature of PC was not responsible for the selective oxidation of it by manganese oxoanions (Figure S4). In addition, the pK a descriptor showed weak associations for the kinetic rates of PC oxidation by manganese oxo-anions (R 2 < 0.70, Figure S5), implying that proton transfer was not the prevailing mechanism for these oxidation processes.…”
Section: Chemicalsmentioning
confidence: 86%
“…For example, the specific energy features mainly focus on the energy change in the protein–ligand recognition process. Similarly, the quantum chemical descriptors 139 of molecules are inextricably linked to the inner energy, such as the energy of the highest occupied molecular orbital ( E HOMO ), the energy of the lowest unoccupied molecular orbital ( E LUMO ), the energy difference between those orbitals ( E GAP ), electronegativity ( χ ), and so on. The protein–ligand interaction fingerprint is also proposed in imitation of molecular fingerprints.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Intermolecular electrostatic descriptors bonding of hydrogen solvent-accessible negatively or positively charged atomic surface regions have also been used as a data source. As derivative quantities like absolute hardness, the energies of the highest occupied and lowest empty molecule orbitals form important quantum chemical descriptors [33][34][35][36][37][38] .…”
Section: Electrostaticmentioning
confidence: 99%